2020
DOI: 10.1097/eja.0000000000001149
|View full text |Cite
|
Sign up to set email alerts
|

Two-handed jaw thrust decreases postoperative sore throat in patients undergoing double-lumen endobronchial intubation

Abstract: BACKGROUND Tracheal intubation using a double-lumen endobronchial tube (DLT) causes postoperative sore throat. OBJECTIVE To determine the effect of two-handed jaw thrust on postoperative sore throat in patients requiring insertion of a DLT. DESIGN A randomised study. SETTING A tertiary teaching hospital from December 2017 to May 2018. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
0
12
2
Order By: Relevance
“…The protective effect of jaw thrust on the severity of sore throat was observed mainly at postoperative 24 hours, which is consistent with the previous investigation regarding double-lumen endobronchial intubation. 11 This study showed no significant decrease in severity of sore throat in the early stage—postoperative 2 and 4 hours—of the postoperative period compared with the aforementioned investigation. 11 Sore throat may be influenced by either the different types of surgical procedure or postoperative pain control in the post anaesthesia care unit.…”
Section: Discussioncontrasting
confidence: 54%
See 4 more Smart Citations
“…The protective effect of jaw thrust on the severity of sore throat was observed mainly at postoperative 24 hours, which is consistent with the previous investigation regarding double-lumen endobronchial intubation. 11 This study showed no significant decrease in severity of sore throat in the early stage—postoperative 2 and 4 hours—of the postoperative period compared with the aforementioned investigation. 11 Sore throat may be influenced by either the different types of surgical procedure or postoperative pain control in the post anaesthesia care unit.…”
Section: Discussioncontrasting
confidence: 54%
“…11 This study showed no significant decrease in severity of sore throat in the early stage—postoperative 2 and 4 hours—of the postoperative period compared with the aforementioned investigation. 11 Sore throat may be influenced by either the different types of surgical procedure or postoperative pain control in the post anaesthesia care unit. More severe pain and additional rescue analgesics administered at the immediate postoperative period in the PACU may have blunted the protective effect of jaw thrust.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations